2008
DOI: 10.1007/s12098-008-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Amebic cerebral abscess mimicking bacterial meningitis

Abstract: We report a case of an amebic brain abscess in a 2-year-old girl, with symptoms mimicking bacterial meningitis with no evidence of disease elsewhere. Histological evaluation of the abscess revealed the organisms, and the abscess regressed in response to specific medical treatment. This article reviews the rarity of these abscesses and difficulty in the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…A clinical case of a 31-year-old man in Thailand describes an amebic abscess located in the right occipital lobe, concomitantly with acute supurative meningitis (Viriyavejakul and Riganti 2009). In the USA, a case was reported of a 2-year-old girl who had multiple brain abscesses in the right cerebral peduncle and in both hemispheres, with abundant inflammatory infiltrate, which came to be confused with bacterial meningitis (Sayhan Emil et al 2008). Based on these data and our results, we suggest that E. histolytica possibly shares membrane antigens and therefore some pathogenic mechanisms with N. fowleri.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A clinical case of a 31-year-old man in Thailand describes an amebic abscess located in the right occipital lobe, concomitantly with acute supurative meningitis (Viriyavejakul and Riganti 2009). In the USA, a case was reported of a 2-year-old girl who had multiple brain abscesses in the right cerebral peduncle and in both hemispheres, with abundant inflammatory infiltrate, which came to be confused with bacterial meningitis (Sayhan Emil et al 2008). Based on these data and our results, we suggest that E. histolytica possibly shares membrane antigens and therefore some pathogenic mechanisms with N. fowleri.…”
Section: Resultssupporting
confidence: 69%
“…Because cerebral infections by bacteria have a medical profile similar to that of protozoans (including headaches, partial muscular weakness, lethargy, and dizziness), diagnosis is often difficult (Sayhan Emil et al 2008;Peralta-Rodriguez and Ayala-Oviedo 2009). Nevertheless, computerized axial tomography (CAT scans) and nuclear magnetic resonance (MRI) both provide data that can lead to the detection of this malady in 100% of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Other group of patients at risk of unusual pathogens are the immigrants from underdeveloped countries, they can have, in addition to those pathogens affecting inmunocompromised patients, other pathogens like Taenia, E. histolytica, Schistosoma, Echinococcus, and Paragonimus. [26,[65][66][67][68][69][70][71] In the Nathoo et al [4] series (the biggest reported), it was found that majority of patients undergoing surgery (53.2%) had isolation of a single organism, being the commonest the gram-positive organisms: S. aureus and Staphylococcus epidermidis, especially in traumatic BA. Streptococcus milleri isolates were predominant in patients with paranasal sinusitis, whereas Proteus mirabilis was most commonly isolated in otogenic infections.…”
Section: Etiologymentioning
confidence: 99%
“…Surgical intervention may be in the form of pus drainage or total excision of the abscess wall and is indicated in cases of a large, multiloculated abscess, no response to antibiotics, mass effect, poor Glasgow Coma Scale score, and development of new abscesses. [11,13,14,15] But our patient succumbed to the fuminant infection before the drugs could be administered.…”
Section: Discussionmentioning
confidence: 94%